2009
DOI: 10.1242/dev.033324
|View full text |Cite
|
Sign up to set email alerts
|

Abi plays an opposing role to Abl inDrosophilaaxonogenesis and synaptogenesis

Abstract: Abl tyrosine kinase (Abl) regulates axon guidance by modulating actin dynamics. Abelson interacting protein (Abi), originally identified as a kinase substrate of Abl, also plays a key role in actin dynamics, yet its role with respect to Abl in the developing nervous system remains unclear. Here we show that mutations in abi disrupt axonal patterning in the developing Drosophila central nervous system (CNS). However, reducing abi gene dosage by half substantially rescues Abl mutant phenotypes in pupal lethality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 71 publications
3
55
0
Order By: Relevance
“…This interaction was recently shown to be required for neurite outgrowth in mammalian cell and zebrafish models of SMA (Li et al 2015). Orthologs of the Abi protein appear to have important roles in neurogenesis via the regulation of actin dynamics (Proepper et al 2007;Lin et al 2009;Liebau et al 2011). Dominant mutations in GARS cause the distal neuropathy Charcot-MarieTooth disease type 2D, and recent observations suggest that GARS may colocalize with SMN in human cells (Motley et al 2010;Drew et al 2011;Grice et al 2015).…”
Section: Rna Signatures Of Diseasementioning
confidence: 99%
“…This interaction was recently shown to be required for neurite outgrowth in mammalian cell and zebrafish models of SMA (Li et al 2015). Orthologs of the Abi protein appear to have important roles in neurogenesis via the regulation of actin dynamics (Proepper et al 2007;Lin et al 2009;Liebau et al 2011). Dominant mutations in GARS cause the distal neuropathy Charcot-MarieTooth disease type 2D, and recent observations suggest that GARS may colocalize with SMN in human cells (Motley et al 2010;Drew et al 2011;Grice et al 2015).…”
Section: Rna Signatures Of Diseasementioning
confidence: 99%
“…We showed that homozygous deletion of mouse Abi2 results in abnormal phenotypes in the eye and braintissues with high Abi2 expression (8). Drosophila embryos lacking both maternal and zygotic abi exhibit embryonic lethality and collapse of axonal patterning (20). In contrast to Abi2, Abi1 exhibits widespread expression (8).…”
mentioning
confidence: 92%
“…Ena localization is disrupted by the absence of Abl, implying that Ena works downstream of Abl (Grevengoed et al, 2003). Recently, it has been shown that Abl interacting protein 1 (Abi1), first identified biochemically in mammalian cultured cells, acts as an antagonist of Abl signaling during axonogenesis through the modulation of F-actin distribution (Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%